Influence of inhomogeneity of lithium-ion transport within the anode/electrolyte interface on mossy lithium formation - Ko, Chi-Jyun; Chen, Chih-Hung; Chen, Kuo-Ching (Journal of power sources, 2023)
The lithium dendrite issue greatly hinders the development of high-energy-density batteries using lithium metal as the anode. Many attempts over the past decades have been made to resolve the lithium dendrite formation. Whereas the root-growing lithium whiskers at the low deposition rate regime and the fractal lithium dendrite at the high deposition rate regime are well investigated, the growth of mossy dendrites at normal charge conditions is not fully understood so far. This work proposes a phase-field method for simulating the mossy dendrite formation. By taking into account two kinds of lithium-ion migration behaviors in the solid electrolyte interphase (SEI), the fast migration pathway at the fractured SEI versus the slow migration pathway at the intact SEI, our simulation results reveal that the inhomogeneity of lithium-ion migration mechanism within the anode/electrolyte interface is the key to the formation of mossy lithium dendrites. [Display omitted] •The formation of mossy lithium dendrites is investigated in phase-field simulations.•Two Li-ion migration pathways across the anode/electrolyte interface are proposed.•SEI mechanical instability is identified as a key factor for mossy dendrite growth.•Correlation among cracks, Li-ion pathway and local current density in SEI is analyzed.